Sengon Biomass Carbon Stock in Tradisonal Agroforestry land Tipe; Climate Change Implication - Ohorella, Syarif; Febriadi, Ihsan; Sangadji, Zulkarnaen (Agrikan Jurnal Agribisnis Perikanan, 2022)
This research was conducted on agroforestry land in Kampung Della, Selemkay District, Tambrauw Regency, West Papua. The research objectives were (1) to estimate the biomass and carbon stored potential of sengon stands and (2) to determine the allometric equation of biomass to estimate the carbon stored potential of sengon stands on agroforestry land types. Biomass measurements were carried out using the destructive method on 2 sample trees with a diameter of 32 cm and 12 cm. The components of biomass measured were the above ground biomass, namely stems, branches, twigs and leaves. Laboratory tests were carried out to determine the dry weight of the biomass. From these results an allometric model was created to estimate carbon stocks. The best equation was chosen using regression analysis based on the highest R-Sq value. The results of research on sengon stands showed that there were differences in the carbon content of tree parts (stems, branches, twigs and leaves). The highest carbon content is in the stem and the smallest in the leaves. The total carbon content is 0.3091 ton C/ha. The selected biomass estimation model for sengon stands on the stem section was W = 0.762 D 1.288, the branch section was W = 0.075 D 1.549, the twig section was W = 0.011 D 1.948 and the leaf section was W = -5.379 + 0.485 D. Meanwhile the model selected for total biomass is W = 0.623 D 1.471.